2009
DOI: 10.2223/jped.1876
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between childhood underweight and dental crowding in deciduous teething

Abstract: ResumoObjetivo: Investigar a relação entre o déficit antropométrico infantil e apinhamento dentário na dentição decídua. Métodos:Foram avaliadas 794 crianças de 3 a 5 anos de idade, de ambos os sexos, matriculadas em pré-escolas públicas da cidade de São Luís (MA). Realizou-se amostragem probabilística por conglomerado em único estágio. Desenvolveu-se estudo transversal com aplicação de questionário, exame de oclusão dentária e avaliação antropométrica na população do estudo. O apinhamento dentário, caracteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 13 publications
0
10
0
7
Order By: Relevance
“…13 These rates may have therefore resulted in a lower CP gain and in chronic malnutrition among the children of this sample. According to Thomaz and Valença, 11 malnourishment results in delayed bone maturation, and can therefore be associated with a higher prevalence of malocclusion in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 These rates may have therefore resulted in a lower CP gain and in chronic malnutrition among the children of this sample. According to Thomaz and Valença, 11 malnourishment results in delayed bone maturation, and can therefore be associated with a higher prevalence of malocclusion in children.…”
Section: Discussionmentioning
confidence: 99%
“…The literature has also shown that nutritional deficiency during child growth and development causes a delay in the ossification centers, and may contribute to poor skeletal and dental formations. 10,11 Moreover, the Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript. modern human skull and face have become smaller with evolution, especially in terms of anteroposterior length and vertical height.…”
Section: Introductionmentioning
confidence: 99%
“…Porém, as alterações congênitas e de desenvolvimento, como os Nódulos de Bohn e Pérolas de Epstein foram vistas com alguma freqüência nesse grupo, totalizando 2% do total de anomalias. Tais achados são as alterações mais comuns em bebês, e na grande maioria das vezes resolvem-se sozinhas sem necessidade de tratamento [9][10][11][12][13][14][15][16][17] .…”
Section: Discussionunclassified
“…O crescimento e desenvolvimento de uma criança são condicionados pela herança genéti ca, sendo fortemente infl uenciados pelo meio ambiente, sobretudo no que se refere à instalação de doenças e à qualidade da nutrição. Por essa razão, as ações direcionadas ao atendimento de crianças devem priorizar a promoção da saúde, seguida da prevenção, diminuindo, assim, o risco de desenvolvimento de afecções [6][7][8][9][10] .…”
Section: Rezende Et Al -Erupção Dentária Em Bebês De Riscounclassified
“…A. F. et al evaluated that malnourished children having habit of thumb sucking showed dental crowding describing that the use of pacifiers decreases the occurrence of dental crowding. 3 Thomas E. B. A. F. et al studied the association of malnutrition and dental crowding, concluded that the subjects with malnutrition associated with habit of mouth breathing showed dental crowding ,describing the habit was associated with dental crowding .…”
Section: Discussionmentioning
confidence: 99%